MULTIDIMENSIONAL LAYERS OF DOMESTIC VIOLENCE IN CONTEMPORARY INDIA: AN ANALYSIS OF SOCIAL, CULTURAL AND LEGAL ASPECTS - Grewal, Upendra; Rani, Kalpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Domestic violence is a serious and multidimensional social problem in contemporary India, deeply rooted in patriarchal structures, cultural traditions and legal systems. This study attempts to understand the causes, forms and effects of domestic violence by analysing its various layers. The main objective of the research is to understand the complex nature of domestic violence from social, cultural and legal perspectives and to present effective solutions for its elimination. From a social perspective, this study identifies patriarchy and gender inequality as the primary causes of domestic violence. It emphasizes how family structures and conservative beliefs prevalent in society prevent victims from seeking justice and help. Under cultural aspects, the influence of caste, religion and regional variations further complicates the problem. It is observed that many traditional practices and beliefs make violence acceptable or ignore it as an internal matter of the family. From a legal perspective, the study assesses the effectiveness of the Domestic Violence Prevention Act, 2005 and other related laws. It also analyses how the shortcomings of the justice system and law enforcement agencies hinder victims from getting justice. Along with this, the lack of rehabilitation and mental health support creates new challenges for the victims. The research suggests that social awareness, policy reforms and strengthening of legal mechanisms are required for the prevention and elimination of domestic violence. It is also imperative to promote community participation and counselling services to provide protection and justice to the victims. The study concludes that domestic violence should not be considered only as an individual problem, but should be seen as a comprehensive social challenge and integrated efforts should be made to solve it.